2013
DOI: 10.1051/pmed/2013031
|View full text |Cite
|
Sign up to set email alerts
|

Développement et évaluation d’une activité de formation continue adaptée aux infirmières et infirmiers en traumatologie

Abstract: Manuscrit soumis le 18 mai 2011 ; commentaires éditoriaux formulés aux auteurs le 26 juillet 2011 ; accepté pour publication le 21 décembre 2012 Résumé -Contexte : La pratique infirmière en traumatologie est complexe. Pour cette raison, la formation continue (FC) s'avère essentielle au développement et au maintien des compétences des infirmières oeuvrant dans ce champ de pratique. But : L'étude visait à développer et évaluer une activité de FC pour les infirmières oeuvrant en traumatologie au service des urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…The relationship between gender and continuing education participation during the last 3 years is significant ( p value = 0.031 > 0.05). This finding is in line with the study conducted by Marceau et al (2013) which showed that 67% of participants in a continuing education activity for trauma nurses were female.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between gender and continuing education participation during the last 3 years is significant ( p value = 0.031 > 0.05). This finding is in line with the study conducted by Marceau et al (2013) which showed that 67% of participants in a continuing education activity for trauma nurses were female.…”
Section: Discussionsupporting
confidence: 91%
“…That improvement could result from the feedback they received during the individual clinical support sessions, which they said it helped them to enhance their pain management skills. Other studies found that pain management CE had a positive effect on nurses' knowledge (Abdalrahim, Majali, Stomberg, & Bergbom, 2011;AlReshidi, Long, & Darvill, 2018;Keen et al, 2017;Machira, Kariuki, & Martindale, 2013;Marceau, 2009;McNamara, Harmon, & Saunders, 2012). For example, a recent systematic review of the impact of educational programs on nurses' post-operative pain management for children (AlReshidi, Long, & Darvill, 2018) found nine studies showing a significant improvement of nurses' knowledge, with eight of them demonstrating good evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study by Marceau (2009) evaluating traumatology CE needs and involving a CE activity with nurses working in an emergency context showed that CE increased knowledge and maintained it over time, even in a complex care environment. The CE needs assessment and variety of teaching methods used by Marceau (2009) underscored the effectiveness of customized CE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation